PENGARUH STRATEGI KWL (KNOW-WANT TO KNOW-LEARNED) BERBANTUAN WEBSITE LET’S READ TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SD DI KECAMATAN KEMAYORAN - Nursifa Fauziah; Gusti Yarmi; Dina Rahmi Darman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of the KWL (Know-Want to Know-Learned) strategy assisted by the Let's Read website on the reading comprehension skills of fourth-grade elementary school students. The focus of this study is on interpretive comprehension. The research method used is quantitative with a Posttest Only Control Group Design. The population in this study is all students at the Kemayoran District Public Elementary School. The sample was selected using cluster random sampling, resulting in SDN Kemayoran 11. Class IV-B was selected as the experimental group and IV-A as the control group, with each class consisting of 20 students. Data collection was conducted using a multiple-choice test instrument. The data were analyzed using the Independent Sample t-test hypothesis test at a significance level of 0.05. The results of the data analysis showed that the Sig. (2-tailed) value was 0.007 < 0.05, so H0 was rejected. It can be concluded that the KWL (Know-Want to Know-Learned) strategy assisted by the Let’s Read website has a significant effect on the interpretive reading comprehension skills of fourth-grade students in Kemayoran District.